INFORMATION ASYMMETRY, EARNINGS AGGRESSIVENESS AND COST OF EQUITY: THE MODERATING ROLE OF INVESTOR PROTECTION - Febriyanti, Erika; Ardiyani, Komala; Kushermanto, Andi; Ulum, Akhmad Samsul (Universitas Bunda Mulia, 2025)
Background: The phenomenon of recent years shows an increase in the number of companies that go public. This condition indicates that more and more companies want to obtain funding through the capital market with the aim of attracting investors to invest their capital. Investors invest funds for the purpose of getting a return, while the company expects the cost of equity. Objective: This study aims to examine the effect of information asymmetry and earnings aggressiveness on the cost of equity, and examine the moderating role of investor protection on the relationship between information asymmetry and earnings aggressiveness on the cost of equity.Research Methods: The research sample is LQ-45 indexed companies on the Indonesia Stock Exchange for the period 2018-2022. 115 research data were analyzed using Partial Least Square (PLS) - Structural Equation Model (SEM).Research Results: Shows that information asymmetry has a negative effect on the cost of equity while earnings aggressiveness has a positive effect on the cost of equity. Investor protection does not moderate the effect of information asymmetry on cost of equity, but weakens the relationship between earnings aggressiveness and cost of equity. Earnings aggressiveness practices are in line with the cost of equity, if balanced with good governance practices. Investor protection needs to be maintained so that the practice of earnings aggressiveness can be minimized so that the cost of equity can be reduced.Originality/Novelty of Research: This research adds investor protection as a moderating variable for information asymmetry and earnings aggressiveness with cost of equity